The most important educational institutions that contributed to the scientific and intellectual movement of the Arab Islamic state in the Umayyad era (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The scientific and intellectual movement witnessed by the Arab Islamic state, which began in the Umayyad era and reached its peak of success and prosperity in the Abbasid era, would not have been possible without the efforts made by the non-Arab peoples and nations who contributed to this movement through their educational institutions that were spread in the region within the Arab Islamic conquest to her. These institutions of all kinds (schools, monasteries, private offices) had a great impact and great merit on the Arab-Islamic civilization that cannot be ignored or denied, Where these institutions contributed to laying the first building block of the Arab- Islamic civilization, which the scientific and intellectual movement of the Arab- Islamic state was launched through the various sciences that it was studying and the various books that it acquired and took care of in theology , medicine, philosophy, mathematics and other sciences, these sciences, which were a mixture of Greek civilization and Persian Civilization, enabled the Muslim Arabs to learn about the civilizations and cultures of other peoples and nations after they moved and Arabized these books from their original language into the Arabic language .